Heterogeneous Condensation for Abatement of Sulfuric Acid Aerosol and Water Saving - Rui Zhang; Xiaodong Si; Lingling Zhao; Linjun Yang; Hao Wu (Journal of Chemistry)
Based on the fundamentals of heterogeneous nucleation, a method to eliminate sulfuric acid aerosol associated with water recycling in the process of limestone-gypsum desulfurization was investigated. The supersaturated environment was achieved in a heat exchanger. Numerical calculation shows that high temperature drop and relative humidity are conducive to the formation of supersaturated vapor environment, and vapor heterogeneous condensation can improve the removal efficiency of sulfuric acid aerosol. Experimental results indicate that the critical supersaturation degree of the sulfuric acid aerosol is found in inverse proportion to their sizes and the removal efficiency of sulfuric acid aerosol could be increased by about 20%. The theoretical and the actual condensable water mass values have been also studied in detail. The mass of condensed water produced by the experiment system is 0.0440 kg/(Nm3·h) as the temperature drop is 5°С, and the most suitable temperature drop is about 1∼2°С for water scarce area. High temperature and humidity reveal a huge potential to recycling water.